Kewenangan Penggunaan Kekuatan oleh Korps Brimob Polri dalam Penanganan Rusuh Massa Berdasarkan Prinsip Hukum Pidana - Muhammad S.Gani; Roy Marthen Moonti; Marten Bunga; Muslim A. Kasim (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
This research aims to analyse the authority of the Police Mobile Brigade Corps (Brimob) in handling mass riots and examine the implementation of criminal law in evaluating the actions taken during the operation. This research departs from the importance of ensuring that every action of law enforcement officials, especially Brimob, remains within the corridors of Indonesian positive law and is oriented towards the principles of human rights. The results show that the Brimob Corps has the legal authority under Law No. 2 of 2002 on the National Police of the Republic of Indonesia to deal with high-level situations, including mass riots. In carrying out its duties, Brimob is authorised to use coercive measures, but must still pay attention to the principles of necessity, proportionality, legality, and accountability. The implementation of criminal law is an important instrument in evaluating Brimob's actions, by assessing whether the use of force meets the elements of legal justification such as forced defence or official orders, in accordance with the Criminal Code and human rights principles. It is suggested that there is a need to improve legal training for Brimob members on the limits of the use of force and the implementation of criminal law principles in emergency situations. In addition, it is necessary to strengthen internal and external evaluation mechanisms, including cooperation with independent institutions such as Komnas HAM, to maintain transparency and accountability. Thus, the rule of law and the protection of human rights can be better upheld in every operation to handle mass riots by Brimob officers.